Strong Influence of Baseline Respiration in an Oligotrophic Coastal Ecosystem - Vikström, Kevin; Bartl, Ines; Karlsson, Jan; Wikner, Johan (Frontiers in Marine Science, 2020)
Respiration is a key metabolic process in the marine environment and contemporary phytoplankton production is commonly assumed the main driver. However, respiration in the absence of contemporary phytoplankton production, termed baseline respiration, can influence the energetics of an ecosystem and its sensitivity to hypoxia. Direct studies of baseline respiration are currently lacking. This study aims to obtain a first estimate of baseline respiration in a sub-arctic estuary and determine its contribution to plankton community respiration. Four approaches used to define baseline respiration determined the average rate to be 4.1 ± 0.1 (SE) mmol O2 m-3 d-1. A hypsographic model at the basin scale accounting for seasonal variation estimated an annual contribution of 30% baseline respiration to planktonic respiration. There was no correlation between plankton respiration and phytoplankton production, but a significant linear dependence was found with the total carbon supply from phytoplankton and riverine input. The sum of dissolved organic carbon transported by rivers, provided by both benthic and pelagic algae, could sustain 69% of the annual plankton respiration, of which as much as 25% occurred during winter. However, only 32% of the winter season respiration was explained, indicating that unknown carbon sources exist during the winter. Nitrification had a negligible (≤ 2.4%) effect on baseline respiration in the system. The results show that baseline respiration accounted for a significant percentage of coastal plankton respiration when allochthonous sources dominated the carbon supply, weakening the respiration-to-phytoplankton production relationship.